MARKET OUT LOOK ON COMMUNITY TOURISM IN KERALA - Vinay Raj R (SAJMMR: South Asian Journal of Marketing & Management Research, 2013)
Kerala (Malayalam: Kēra ḷ am) is a state in south India. It was created on 1 November 1956, with the passing of the States Reorganization Act bringing together the areas where Malayalam is the dominant language. The state has an area of 38,863 km 2 and is bordered by Karnataka to the north, Tamil Nadu to the south and the east and the Arabian Sea towards the west. Thiruvananthapuram is the capital of Kerala. Kochi and Kozhikode are the other major cities. Since independence, Kerala was managed as a democratic socialist welfare economy. Since the 1990s, liberalization of the mixed economy allowed onerous License Raj restrictions against capitalism and foreign direct investment to be lightened, leading to economic expansion and job creation. Traditional industries manufacturing such items as coir, handlooms, and handicrafts employ around one million people. Community tourism is not always successful, and perhaps we could begin to look at failures as pathways to success. Rural community tourism takes place in already marginalized areas. Created with good intentions, community-based tourism projects are abandoned when political pressures rise, jealousies intensify or the heralded eco tourists don't arrive. Developers may talk of 'integrating communities into tourism,' but rarely do they visit a community and ask what it is locals want. Instead, operations are imposed in an all too familiar top-down fashion.